1992
DOI: 10.1128/jcm.30.2.323-329.1992
|View full text |Cite
|
Sign up to set email alerts
|

Controlled comparison of the BacT/Alert and BACTEC 660/730 nonradiometric blood culture systems

Abstract: In a collaborative study at three university hospitals, the recovery of microorganisms and the speed of detection of microbial growth by the BacT/Alert (Organon Teknika Corporation, Durham, N.C.) and BACTEC 660/730 (Becton-Dickinson Diagnostic Instrument Systems, Sparks, Md.) nonradiometric blood culture systems were compared. A total of 5,918 comparisons were made between BacT/Alert aerobic and BACTEC NR 6A bottles and 5,992 comparisons were made between BacT/Alert anaerobic and BACTEC NR 7A bottles. Each bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
3
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 14 publications
5
66
3
1
Order By: Relevance
“…In a large controlled clinical comparison of VITAL and BACTEC NR-600 blood culture systems for the detection of sepsis in children [5], the BACTEC PEDS PLUS bottle performed significantly better than the VITAL AER bottle in detecting the growth of bacteria and yeast from children. When the authors evaluated cultures that had a volume advantage in one system over the other, PEDS PLUS bottles retained a statistical advantage even when VITAL AER bottles received more blood.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a large controlled clinical comparison of VITAL and BACTEC NR-600 blood culture systems for the detection of sepsis in children [5], the BACTEC PEDS PLUS bottle performed significantly better than the VITAL AER bottle in detecting the growth of bacteria and yeast from children. When the authors evaluated cultures that had a volume advantage in one system over the other, PEDS PLUS bottles retained a statistical advantage even when VITAL AER bottles received more blood.…”
Section: Discussionmentioning
confidence: 97%
“…While in our study standard media flacT/Alert bottles were used in comparison with the VITAL bottles, Zaidi et a1 [5] compared VITAL AER bottles with resin-containing PEDS PLUS bottles. Although it is suggested that resin-containing media are superior for detecting microorganisms, especially for patients on antimicrobial therapy, Zaidi et a1 (51 found that PEDS PLUS medium was also better at detecting Staphylococci and all microorganisms combined even for patients not on antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These differences were not statistically significant. Wilson et al did not find a difference in staphylococcal isolation when comparing BacT/Alert and BACTEC NR 660/730 [2]. However, BacT/Alert was less effective in recovering Staphylococcus aureus isolates in a trial comparing BacT/Alert with Difco ESP [9].…”
Section: Discussionmentioning
confidence: 98%